The indigenous domestic ruminant genetic resource - Rege, J.E.O.; Yapi-Gnoare, C.V.; Tawah, C.L. (South African Society of Animal Science, 1996)
Africa is endowed with a large number of indigenous domestic animals which supply animal protein, income and investment to most rural smallholders and provide the only practical means of exploiting vast areas of the continent where crop prouction is not possible and exotic animals caanot survive. Genetic diversity in these animal populations consitute a repertoire of genes essential for the Development of sustainable animal production. There are at least 150, 125, 90 and 40 "breeds" or strains of cattle, sheep, goats and dromedary camels in Africa, representing over 18, 15, 28 and 80 percent of the global total for the four respective species. This paper summarizes the available genetic resources by species and geographical location.